Src SH3/2 Domain-mediated Peripheral Accumulation of Src and Phospho-myosin Is Linked to Deregulation of E-cadherin and the Epithelial-Mesenchymal Transition - Avizienyte, Egle (The American Society for Cell Biology, 2004)
Elevated Src kinase in epithelial cancer cells induces adhesion changes that are associated with a mesenchymal-like state. We recently showed that Src induces dynamic integrin adhesions in KM12C colon cancer cells, whereas E-cadherin–dependent cell-cell contacts become disorganized. This promotes a fibroblastic-like morphology and expression of the mesenchymal marker vimentin. Furthermore, Src-induced deregulation of E-cadherin, and the associated mesenchymal transition, is dependent on integrin signaling (Avizienyte et al., Nat. Cell Biol. 2002, 4, 632–638), although the nature of downstream signals that mediate these Src- and integrin-dependent effects are unknown. Here we show that the SH2 and SH3 domains of Src mediate peripheral accumulation of phospho-myosin, leading to integrin adhesion complex assembly, whereas loss of SH2 or SH3 function restores normal regulation of E-cadherin and inhibits vimentin expression. Inhibitors of MEK, ROCK, or MLCK also suppress peripheral accumulation of phospho-myosin and Src-induced formation of integrin-dependent adhesions, whereas at the same time restoring E-cadherin redistribution to regions of cell-cell contact. Our data therefore implicate peripheral phospho-myosin activity as a point of convergence for upstream signals that regulate integrin- and E-cadherin–mediated adhesions. This further implicates spatially regulated contractile force as a determinant of epithelial cell plasticity, particularly in cancer cells that can switch between epithelial and mesenchymal-like states.